Conceptual Networks and Research Trends in Javanese Islam Studies: A Bibliometric Analysis - Gedong Maulana Kabir (Javanologi: International Journal of Javanese Studies, 2025)
This study aims to map the landscape of Javanese Islamic studies quantitatively to overcome the limitations of narrative analysis, which often only focuses on specific issues. The hypothesis proposed is that there is a paradigmatic stagnation, where the study is still trapped in the shadow of Clifford Geertz's theory. Using bibliometric analysis and visualization methods from the Biblioshiny application, this study processed 445 relevant documents from the Scopus dataset from 1911 to 2025. The study results show that although this research continues to develop in terms of collaboration and publication, the contributors are dominated by authors, affiliations, and publication sources in Indonesia, but international authors dominate the most productive single authors and co-citation networks. The co-occurrence and co-citation network analyses validate the hypothesis that the study remains under the shadow of the Geertz paradigm, with the abangan, santri, and priyayi issue as the central debate. Nonetheless, the study also identifies emerging themes, such as tradition, slametan, and syncretism. In conclusion, Javanese Islamic studies are a stable field, but they are still tied to the old paradigm. Therefore, future research is suggested to explore promising themes, such as the role of women, the Islamic industry, and the influence of the politics of religion (dominated by Islam) in Indonesia, to open an increasingly dynamic and relevant research direction related to Javanese Islam.